Experimental Disciplines: Challenges Faced by Teachers and Students of the Licentiate Course at the Federal Institute of Education, Science and Technology of Piauí - Welda Silva Nunes, Francisca; Santos Lima, Aylla; de Assis Pereira Neto, Francisco (Seven Editora, 2023)
Chemistry is the science that studies the transformations that involve matter and energy, based on experimental practices of the concepts that are addressed in the classroom. With the COVID-19 pandemic, education took new directions towards technologies, due to the need to continue with classes even in extreme periods, educational didactics involving the use of technologies had to be adapted both to the educator and the student, making them both adhere to remote teaching. In the classes referring to the experimental chemistry practices, the chemical experiments were carried out through remote classes, which caused an effect of astonishment on the teachers and students, who had to adapt these activities to the imposed and necessary contents of the curriculum of the chemistry course. to the virtual world, so numerous challenges arose during this process. Therefore, this article will address, through the verification of data analysis of a questionnaire aimed at teachers and students, the main challenges faced in practical chemistry classes during this period of pandemic, making a comparison with practical classroom classes, concluding that there were advantages and disadvantages in this process. DOI: 10.56238/pacfdnsv1-041